Key Issues in Forging Credible Corporate Social Responsibility Partnerships - Khalid Nasir; Shadab Fariduddin (JISR Management and Social Sciences & Economics, 2010)
Corporate Social Responsibility (CSR) is a burgeoning practice where businesses in Pakistan are becoming increasingly interested, active and innovative. Spread of CSR has created necessity for corporate organizations to enter into purposeful partnerships with the development sector organizations. These partnerships enable the corporate sector to become an active social investor while expanding development sector's reach and impact. However, there is a disconnect in forming partnerships owing to lack of awareness and misconception on both sides about each other's performance and intent to carry out triumphant CSR projects. This research highlights the key issues that inhibit the credible CSR partnerships. The study concludes that CSR-centricity is gaining traction and the lack of understanding about each others' motivations does inhibit formation of credible CSR partnerships owing to four top key issues and a dissimilar set of intentions to perform CSR. The study also highlights corporate philanthropy as the top CSR initiative and environment conservation, education and health care as top causes for CSR.